Peran Pendidikan Kewarganegaraan dalam Membentuk Karakter Bangsa - Wardatul Ilmi; Syamzaimar Syamzaimar (Jurnal Pendidikan dan Kewarganegara Indonesia, 2026)
The role of citizenship education is fundamental in internalizing the values of nationalism and ethics within a society. This research is motivated by the increasing challenges of globalization and moral degradation that threaten the national identity of the younger generation. The primary objective of this study is to analyze the strategic role of citizenship education in shaping and strengthening national character within the Indonesian context. The research employs a qualitative descriptive method, utilizing literature reviews and thematic analysis of educational policies and social phenomena. The findings indicate that citizenship education serves as a vital instrument not only for transferring political knowledge but also for fostering civic disposition, including integrity, tolerance, and social responsibility. Furthermore, the integration of local wisdom within the curriculum significantly enhances the effectiveness of character building. The implications of this study suggest that a revitalized citizenship education curriculum, which adapts to digital era challenges, is essential for maintaining social cohesion. Stakeholders in the education sector must prioritize interactive and participatory pedagogical approaches to ensure that national character values are not merely memorized but practiced in daily life, thereby ensuring the long-term sustainability of the nation's democratic values.